Exploring organizational readiness for lean: Enablers and barriers in public postal services - Mohd Fauzi, Mas Ayu Diana; Hashim, Mimi Zazira; Mansor, Farah Ahlami; Muhammad, Norrini (Journal of Islamic, Social, Economics and Development, 2026)
Lean management has increasingly become a strategic imperative for organizations seeking to enhance efficiency and responsiveness. While traditionally rooted in manufacturing, Lean principles have found relevance in service sectors such as healthcare, education, and logistics. Postal services are undergoing digital and operational transformation to meet evolving customer expectations and competitive pressures. This paper presents a conceptual analysis of the enablers and barriers to Lean implementation in postal services, with specific reference to Pos Malaysia. Drawing from global, ASEAN, and Malaysian contexts, the paper synthesizes existing literature to propose a conceptual framework that identifies top management support, employee engagement and training, digital integration, and organizational culture as key enablers. Conversely, resistance to change, bureaucratic structures, limited Lean knowledge, and resource constraints emerge as significant barriers. The paper concludes with implications for future research and recommendations for effective Lean deployment in the postal sector